Plan de mejoramiento para la empresa EURO - TRADE comercializadora de productos farmacéuticos de la ciudad de Armenia – Quindío (2015)
This project is an improvement plan which focused on improving the different areas of the company Euro - Trade of the city of Armenia - Quindío, for this purpose begins with a situational analysis of the organization which allows you to make a diagnosis of the same, and thus discover the aspects to be taken into account to achieve the increase of the enterprises in all areasadjusting them to the needs of the company, according to its corporate purpose. Diagnosis begins with the collection of the necessary information from the current situation of the company, so we used the survey of officials, survey customers and an interview with the general manager of the company, these tools prominently as a result some weaknesses and threats which must be improved so that the company can be a competitive firm in the sector of distribution and sale of drugs in the region. Once made the diagnosis, we proceeded to the approach of the improvement plan, which included activities, task, indicators and budget for its implementation, in this last possible funding of strategies is analyzed through a credit at a financial institution, with a rate of interest according to the existing ones in the market and are calculated possible fees that must comply with the companyin the same way is made an analysis of the environmental impact that can generate the plan of improvement to the environment. The work ends with conclusions and recommendations, where are reflected the main aspects that need improving the company so that it can operate with a high degree of competitiveness as required by the current business environment.